Association of rs10830963 MTNR1B and rs841853 SLC2A1 Polymorphism with Obesity on Type 2 Diabetes Patients: An Overview of Melatonin Receptor and Transporter - Yanuarita Tursinawati; Arum Kartikadewi; Ari Yuniastuti; R Susanti (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: One of the hormones that plays a role in glucose metabolism of Type 2 Diabetes Mellitus (T2DM) is melatonin. Its genetic variation is believed to play a significant role in the pathophysiology of obese and non-obese T2DM. The role of MTNR1B (melatonin receptor coding gene) and SLC2A1 (Glucose transporter 1/GLUT 1 transporter coding gene) on the risk of obese and non-obese T2DM patients is controversial. This study aims to analyze the association between the rs10830963 MTNR1B and rs841853 SLC2A1 polymorphism to the risk of Javanese obese T2DM.METHODS: This was a cross-sectional study that involved 107 Javanese T2DM patients from primary heath care in Semarang. Furthermore, obese T2DM was defined by a body mass index (BMI) more than 25 kg/m2. The genetic variations examined were rs10830963 MTNR1B and rs841853 SLC2A1 polymorphism by PCR-RFLP methods. Blood biochemistry parameters were also examined. Allele and genotype frequencies of rs10830963 MTNR1B and rs841853 SLC2A1 polymorphisms were analyzed using the x2 test with p≤0.05 and 95% CI.RESULTS: There was a significant association between rs10830963 MTNR1B polymorphisms in obese and nonobese T2DM (p=0.044) and the CG genotype increased the risk of obese T2DM. Furthermore, the allele and genotype frequency of rs841853 SLC2A1 polymorphism in both group had no significant difference, with a p=0.756 and p=0.802, respectively. There was also no significant difference in the biochemical parameters' in both groups of the two genetic variants studied.CONCLUSION: The rs10830963 MTNR1B polymorphism is associated with the risk of obesity in Javanese T2DM patients but not for the rs841853 SLC2A1 polymorphism.KEYWORDS: polymorphism, MTNR1B, SLC2A1, obese, diabetes mellitus